2017
DOI: 10.3389/fphys.2017.00877
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Role of Transient Receptor Potential Ankyrin 1 in a Mouse Long-Lasting Cystitis Model Induced by an Intravesical Injection of Hydrogen Peroxide

Abstract: Chronic inflammatory bladder disorders, such as interstitial cystitis/bladder pain syndrome, are associated with poor quality of life. The exact pathological processes remain unclear, but accumulating evidence suggests that reactive oxidative species (ROS) are involved in urinary bladder disorders. Transient receptor potential ankyrin 1 (TRPA1), the most sensitive TRP channel to ROS, was shown to be responsible for urinary bladder abnormalities and hyperalgesia in an acute cystitis model. However, the roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Agonists of TRPA1 (AITC and CA) increase the bladder contraction, stretch sensitivity, hyperalgesia, and micturition in rats and guinea pigs (37,193,222,589). Moreover, in various OAB models, TRPA1 protein and mRNA expression levels are increased in the bladder and in the DRG neurons innervating it (38,193,221,376,499,539,634,862). This upregulated TRPA1 expression may increase sensory transductions and induce the OAB symptoms.…”
Section: H Trpa1 In the Urogenital Systemmentioning
confidence: 99%
“…Agonists of TRPA1 (AITC and CA) increase the bladder contraction, stretch sensitivity, hyperalgesia, and micturition in rats and guinea pigs (37,193,222,589). Moreover, in various OAB models, TRPA1 protein and mRNA expression levels are increased in the bladder and in the DRG neurons innervating it (38,193,221,376,499,539,634,862). This upregulated TRPA1 expression may increase sensory transductions and induce the OAB symptoms.…”
Section: H Trpa1 In the Urogenital Systemmentioning
confidence: 99%
“…Several subtypes of TRP channels are reportedly major components of the sensory system controlling bladder function in response to diverse stimuli . In rodent cystitis models with nociceptive pain derived from acroline, the metabolite of cyclophosphamide, or H 2 O 2 , the function and/or expression of TRPA1, TRPV1, and TRPV4 has been shown to be accelerated . In this study, expression of TRPV1 and TRPV4 in the mouse bladder submucosa and/or urothelium was induced by oxidative stress from H 2 O 2 , and change in expression was clearly inhibited by HBO treatment (Figure ).…”
Section: Discussionmentioning
confidence: 70%
“…However, there was no significant change in TRPA1 expression in bladder between the sham control and H 2 O 2 ‐treated group (data not shown). This molecule is also focused as a key factor to generate pain and cause bladder dysfunction in response to numerous irritants and ROS, while the alteration in TRPA1 expression under an exposure to H 2 O 2 in this study might be remarkable in the C‐fiber afferent pathway (ie, pelvic dorsal root ganglion) rather than bladder epithelium and submucosa. At least, the current results examined in bladder revealed that the inhibitory effect of HBO on TRP channel expression (eg, TRPV1, TRPV4) could partially contribute to improved voiding function and bladder‐related pain in this chronic cystitis model.…”
Section: Discussionmentioning
confidence: 88%
“…TRP channels are widely expressed in lower urinary tract tissues and play a critical role in the normal micturition reflex (for review: Andersson, 2019). TRPA1 is known to contribute to nociceptive responses evoked by endogenous and exogenous irritants (Oyama et al, 2017), including MGO itself (Bierhaus et al, 2012;Eberhardt et al, 2012). On the other hand, TRPV1 and TRPV4 are involved in bladder activity in response to mechanical or chemical stimulus (Andersson, 2019).…”
Section: Discussionmentioning
confidence: 99%